(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
The world of drug delivery is undergoing a profound transformation. Nowadays, conventional drug delivery systems (DDS) are not mostly used due to their side effects and limited benefits. We have already entered the era of smart DDS (SDDS) which is an innovative wave of therapy that delivers medications precisely where and when required and always in right amounts. The heart of these systems is nanocarriers. These are microscopic transporters engineered to protect and deliver drugs with pinpoint accuracy. These tiny vehicles come in various forms such as liposomes, nanoparticles, quantum dots, dendrimers, carbon nanotubes, and superparamagnetic iron-oxide nanoparticles each offering unique advantages. This controlled delivery shines especially in areas such as cancer and gene therapy, where precision can make the difference between success and setbacks. This review focuses on the design and preparation of the nanocarriers and explore their real-world applications, from targeted tumor treatment to customized gene delivery. It helps in overcoming long-standing limitations posed by conventional drug delivery, SDDS are paving the way for treatments that are not just more effective, but also safer and more personalized. This article also gives information regarding the available marketed products of the nanocarriers along with their manufacturer’s details and also the brand names. With smarter, more responsive systems, the future of disease management looks brighter than ever; bringing us closer to therapies tailored to each individual’s unique needs